Morbidity and mortality of candidaemia in Europe: an epidemiologic meta-analysis. (October 2019) - Koehler, P.; Stecher, M.; Cornely, O.A.; Koehler, D.; Vehreschild, M.J.G.T.; Bohlius, J.; Wisplinghoff, H.; Vehreschild, J.J.
Abstract: Objectives: Candidaemia is a serious hazard to hospitalized patients, but European epidemiological data are restricted to national studies focusing on Northern Europe, population-based surveillance programmes or studies conducted in distinct local areas. The aim was to provide current data on the overall burden and epidemiological development of candidaemia in Europe. Methods: A Web of Knowledge™ search was carried out from January 2000 to February 2019. Appropriate data were collected on total cases, study duration, incidence, species distribution and/or mortality rates. Meta-analysis was performed to pool individual studies. Heterogeneity was examined using the I 2 statistic. Calculations of pooled incidence and mortality rates, subgroup analysis by geographical origin, study period and scenarios were carried out. Daily candidaemia incidence and mortality rates in Europe were extrapolated. Systematic review and meta-analysis were used to determine incidence and mortality of candidaemia in the UN European region. Complete datasets were categorized into population-based and hospital-based epidemiological studies and were analysed separately. Subgroup analyses were performed for geographic distributions and time-dependent developments. Results: In population-based studies, 43 799 cases of candidaemia were diagnosed in 1 885 271 885 person-years, revealing an overall pooled incidence rate of 3.88/100 000. The highest pooled incidence rate was observed in intensive care units (5.5/1000 admissions, Day 30 mortality rate 37%), followed by tertiary care centres (0.96/1000 admissions, pooled Day 30 mortality rate 38%) and the mixed group of teaching and general hospitals (0.52/1000 admissions, pooled Day 30 mortality rate 37%). European incidence of candidaemia was extrapolated to approximately 79 cases per day, of which an estimated 29 patients might have fatal outcome at Day 30. Conclusions: Pooled incidence rates, species distribution and outcome of candidaemia differ considerably between clinical groups, European regions and over time. We observed an increasing overall pooled incidence rate of candidaemia and a higher proportion of Candida spp. other than C. albicans in the current decade in population-based data.